2014
DOI: 10.1155/2014/301410
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofγ-Irradiation and Calcination Temperature of Nanosized ZnO/TiO2System on Its Structural and Electrical Properties

Abstract: ZnO/TiO2 powders were synthesized by sol-gel method using ammonium hydroxide. The effects of calcination temperature (500–1000°C) and gamma rays (with doses from 25 to 150 kGy) on the phases present and their electrical properties were investigated. The results revealed that heating the system investigated at 500°C led to the formation of ZnTiO3-rohom and TiO2-rutile. The degree of crystallinity of the phases produced increased by increasing the calcination temperature. When heating at 1000°C, ZnTiO3-rohom tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…The room temperature irradiation of the as-deposited film shows a gradual decrease in crystallite size with the increase in irradiation fluence. The reduction in grain size due to irradiation has also been observed in some previous studies [44,45]. The decrease in the crystallite size can be related to the change in the strain and the composition due to the mixing of Mn and Al atoms near the interface.…”
Section: Average Crystallite Size (Nm)supporting
confidence: 74%
“…The room temperature irradiation of the as-deposited film shows a gradual decrease in crystallite size with the increase in irradiation fluence. The reduction in grain size due to irradiation has also been observed in some previous studies [44,45]. The decrease in the crystallite size can be related to the change in the strain and the composition due to the mixing of Mn and Al atoms near the interface.…”
Section: Average Crystallite Size (Nm)supporting
confidence: 74%
“…The impedance values of the γ-irradiated nanocomposites are less than the nonirradiated nanocomposites. This could be attributed to the γ radiations' energy releasing more free electrons and/or creating more holes that facilitate the motion of more electrons and, hence, allow the nanocomposites to be more conductive [17].…”
Section: Resultsmentioning
confidence: 99%
“…According to several reports on the effects of gamma irradiation on ZnO nanocomposites, the polymer composites can undergo significant physical changes with different modifications when subjected to γ radiation. These changes can affect the properties of the irradiated polymer composites, such as structural scission or cross-linking, modification of the degree of filler particle aggregation, creation of holes or cavities, modification of band gap values, and/or the formation of more dipoles [14][15][16][17][18][19][20][21][22][23][24][25]. Several scientific research papers in the literature reported the effect of gamma radiation on the physical properties of ZnO, CB, and/or epoxy polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of gamma radiation on the physical properties of polymer nanocomposites have been extensively studied. In general, radiation-induced secession or cross-linking alters the degree of aggregation of filler particles and creates holes or cavities in irradiated composites [4,5].…”
Section: Introductionmentioning
confidence: 99%